American Thoracic Society 2019 Pediatric Core Curriculum. Issue 12 (27th August 2019) - Moore, Paul E.; Boyer, Debra; Perkins, Ryan; Katz, Eliot S.; Castro‐Codesal, Maria L.; MacLean, Joanna E.; Akil, Nour; Esther, Charles R.; Kaslow, Jacob; Lewis, Toby C.; Krone, Katie A.; Quizon, Annabelle; et al.
Abstract: The American Thoracic Society Pediatric Core Curriculum updates clinicians annually in pediatric pulmonary disease in a 3 to 4 year recurring cycle of topics. The 2019 course was presented in May during the Annual International Conference. An American Board of Pediatrics Maintenance of Certification module and a continuing medical education exercise covering the contents of the Core Curriculum can be accessed online at www.thoracic.org .